SiC interdigit detectors for post-accelerated ions generated by laser plasma. (September 2016) - Sciuto, A.; Torrisi, L.; Cannavò, A.; Ceccio, G.; Musumeci, P.; Mazzillo, M.; Calcagno, L.
Abstract: The ion streams emitted from laser generated plasmas and post-accelerated through a high voltage acceleration path, were monitored by solid state 4H-SiC interdigit detectors in time-of-flight configuration. The plasmas are produced by irradiation of an aluminum target through a ns pulsed laser with 10 10 W/cm 2 intensity and 200 mJ pulse energy. Laser-generated plasma exhibits a mean energy of the order of 100 eV per amu. In order to enhance the ion kinetic energy a post acceleration in the range 1 kV–30 kV was employed. In this paper we studied the correlation of the acquired spectra shape with the post acceleration voltage and with the detector polarization condition. An increase in the spectra intensity was observed and studied with increasing both detector reverse bias and post acceleration voltage. Obtained results demonstrate that interdigit 4H-SiC diodes with millimetric size, show a quite good efficiency for ion detection with energy higher than 5 keV and are very promising devices allowing, thanks to their millimetric size, to carry out detectors array systems for the measurement of the spatial distribution of low energy ions generated by pulsed laser-plasmas. Highlights: Millimetric interdigit SiC detectors allows to monitor H and Al ions in the energy range 5–30 KeV. The analytic description of the generated current takes into account the drift and the diffusion component. Array systems can be realized for the monitoring of spatial distribution of low energy ions generated by pulsed laser.